Interpretation in reverse: Remixing the Three Kingdoms. - Wang, Yiwen (Journal of Popular Culture (John Wiley & Sons, Inc.), 2024)
This article investigates online fan video remixes that combine footage from the televisual adaptation of the Chinese classic The Romance of Three Kingdoms, set in ancient China, with soundtracks from the American science fiction film Inception (2010) and the magical fantasy Pirates of the Caribbean (2011). Analyzing the audio‐visual aesthetics of these videos, I propose a reversal of Henry Jenkins's "additive comprehension" framework, which suggests that fan works aim to interpret and complete the original story‐verse. Instead, I argue these videos reverse the process of interpretation through temporal–spatial transportation and corporeal transfiguration with false continuity editing, acousmatic aesthetics, and gravitational disorientation.